Corporate Practice and Financial Stability of Listed Deposit Money Banks in Nigeria - Ali- Momoh, Betty Oluwayemisi; Samson, Fajuyagbe Bamikole; Oluwaseun , Deji-Oyeleye Bosede; Elizabeth , Aduwo Ayomikun; Moses, Suleiman Taiwo (Acta Universitatis Danubius. Œconomica, 2024)
This study examines the effect of corporate practices on the financial stability of listed Deposit Money Banks (DMBs) in Nigeria. Utilizing a quantitative approach, secondary data from the annual reports of ten selected DMBs between 2014 and 2023 were analyzed using statistical tools such as descriptive statistics and a panel regression model of Random effect. The results reveal significant positive effect of, corporate social responsibility expenditure and ethical compliance demonstrates a positive and statistically significant influence on earnings per share, suggesting that increased investment in CSR activities correlates with improved financial performance. Conversely, a negative but significant relationship is observed between employee turnover rate and EPS, indicating adverse effects on financial stability. Furthermore, ethical compliance exhibits a positive association with EPS, underscoring the importance of adherence to ethical standards for financial well-being. Implications of the findings extend to academia and banking practitioners, emphasizing the necessity of integrating CSR initiatives into corporate strategies to enhance financial stability. Mitigating high employee turnover rates and maintaining ethical standards are recommended strategies for bolstering financial performance. Methodologically, the study contributes by employing rigorous statistical methods and model selection techniques. In conclusion, this research sheds light on the relationship between corporate practices and financial stability within Nigerian DMBs, offering empirical evidence and methodological advancements. Recommendations include increasing CSR investment, addressing turnover issues, and upholding ethical standards to bolster financial stability and overall performance in the banking sector.